2017
DOI: 10.1093/ofid/ofx063
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Enterobacteriaceae Infections: Results From a Retrospective Series and Implications for the Design of Prospective Clinical Trials

Abstract: Background.The increasing incidence of multidrug-resistant Gram negatives, such as carbapenem-resistant Enterobacteriaceae (CRE), has resulted in a critical need for new antimicrobials. Most studies of new antimicrobials have been performed in patients with nondrug-resistant pathogens. We performed a retrospective analysis of patients with CRE infections to inform the design of phase 3 clinical trials.Methods.This was a retrospective study at 22 centers in 4 countries. Baseline data, treatment, and outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…This raises an important point of discussion, that is the need for a correct balance between limiting the use of novel agents to delay emergence of further resistance and, at the same time, guaranteeing the most active early therapy in case of severe infection. This is particularly important for CRE, by considering together the following reasons: (1) CRE infections are endemic in several countries [8], (2) there is a frequent delay of active therapy in patients with CRE infections [8], and (3) there is lower survival of patients with severe infections when active therapy is delayed [1]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises an important point of discussion, that is the need for a correct balance between limiting the use of novel agents to delay emergence of further resistance and, at the same time, guaranteeing the most active early therapy in case of severe infection. This is particularly important for CRE, by considering together the following reasons: (1) CRE infections are endemic in several countries [8], (2) there is a frequent delay of active therapy in patients with CRE infections [8], and (3) there is lower survival of patients with severe infections when active therapy is delayed [1]. …”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance is increasing worldwide, and serious infections due to carbapenem-resistant Enterobacteriaceae (CRE) have been associated with increased morbidity and high mortality [18]. In the last decade, the treatment of serious CRE infections was frequently based on the combination of last-resort agents associated with nephrotoxicity, possible subtherapeutic concentrations, and/or intermediate in vitro activity due to limited options and resistance to several classes of antimicrobials [13, 9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbapenem class of antibiotics has a broad spectrum of activity and is indicated for life‐threatening infections and multidrug‐resistant (MDR) organisms . Resistance to carbapenems, such as carbapenem‐resistant Enterobacteriaceae (CRE), has been reported in every state in the United States and has been linked to high mortality and low rates of clinical cure . In order to control and reduce antibiotic resistance, previous studies have identified risk factors such as antibiotic use and intensive care unit (ICU) stay .…”
Section: Introductionmentioning
confidence: 99%
“…3 Resistance to carbapenems, such as carbapenem-resistant Enterobacteriaceae (CRE), has been reported in every state in the United States and has been linked to high mortality and low rates of clinical cure. 4,5 In order to control and reduce antibiotic resistance, previous studies have identified risk factors such as antibiotic use and intensive care unit (ICU) stay. 6 However, we do not know if controlling these risk factors will lead to a decrease in CRE.…”
Section: Introductionmentioning
confidence: 99%